Leveraging Inclusive Business Models to Support the Base of the Pyramid during COVID-19 - Geaneotes, Alexis; Mignano, Kathleen (International Finance Corporation, Washington, DC, 2020)
The COVID-19 crisis is expected to roll back some of the progress made against global poverty over the last two decades, with the greatest impact on individuals at the base of the economic pyramid. Inclusive businesses that expand access to goods, services, and livelihoods for these individuals are responding to the crisis by reorienting and adapting their inclusive business models and operations. This note highlights seven actions that companies are taking to address needs at the base of the pyramid. We present their actions here as examples of what other businesses could do in response to the needs of those at the base of the pyramid.